2016
DOI: 10.1007/s12159-016-0142-y
|View full text |Cite
|
Sign up to set email alerts
|

M2M Potentials in logistics and transportation industry

Abstract: All over the world, road congestion is among the most prevalent transport challenges usually in urban environments which not only increases fuel consumption and emission of harmful gases, but also causes stress for the drivers. Intelligent Transportation System (ITS) enables a better use of the infrastructure by connecting vehicles to other vehicles as well as infrastructure and thus delivers a faster communication opportunity to ensure safe and secure driving. Machine-to-machine (M2M) communication is one of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…M2M communication provides a dynamic resource-sharing mechanism that allows IoT entities to share resources with each other by using artificial intelligence (AI), deep learning (DL), etc. It also provides advanced architecture for the smart communication of IoT devices with each other [43]. The ultramodern architecture is elaborated in Figure 4.…”
Section: Machine-to-machine Communication (M2m)mentioning
confidence: 99%
“…M2M communication provides a dynamic resource-sharing mechanism that allows IoT entities to share resources with each other by using artificial intelligence (AI), deep learning (DL), etc. It also provides advanced architecture for the smart communication of IoT devices with each other [43]. The ultramodern architecture is elaborated in Figure 4.…”
Section: Machine-to-machine Communication (M2m)mentioning
confidence: 99%
“…Cui et al [141] did a literature review and the results showed that almost 25% of big data applications concern monitoring. Cloud computing and sensor networks are two main technologies discussed by Mehmood et al [58], as they can enable machine-to-machine communication amongst logistics equipment and machines. The communication amongst different machines and systems relies on cellular networks to facilitate mobility.…”
Section: Category 3: Control Track and Trace-related Activitiesmentioning
confidence: 99%